Research Progress on the Role of Zinc Finger Protein in Colorectal Cancer - Tang Yu; Jiumei Zhao; Ziwei Li; Chenglong Pan; Jialing Liu; Kepu Zheng; Xiaohao Wang; Yan Zhang (Cancer Reports)
ABSTRACT Background Colorectal cancer is one of the most prevalent malignancies worldwide, with a tendency of increasing incidence in developed countries, which poses a significant threat to the patients' physical and mental health. Recent Findings The process of gene transcription affects the important physiological functions of cells, so the normal expression of transcription factors is an important prerequisite for maintaining cellular homeostasis. Changes in the level of zinc finger proteins, the most prevalent transcription factor, may play an important trigger for the development of colorectal cancer. Different zinc finger proteins play different roles in terms of promoting or inhibiting cancer development. Conclusion This paper briefly reviews the classification, functional characteristics, and expression changes of zinc finger proteins in colorectal cancer, it focuses on how they regulate gene transcription, influence on common signaling pathways, and their potential for translational studies and clinical applications. The objective is to stimulate new ideas for their study of colorectal cancer while also providing foundational information to guide drug development and treatment strategies for colorectal cancer patients in clinical settings.